Schur-convexity for compositions of complete symmetric function dual - Huan-Nan Shi; Pei Wang; Jian Zhang (Journal of Inequalities and Applications, 2020)
Abstract The Schur-convexity for certain compound functions involving the dual of the complete symmetric function is studied. As an application, the Schur-convexity of some special symmetric functions is discussed and some inequalities are established.